Optimal nonlinear redistributive taxation and public good provision in an economy with Veblen effects - Luca Micheletto (Uppsala University, Department of Economics, 2009)
This paper deals with the consequences of the assumption of negatively interdependent preferences for the shape of the optimal nonlinear income tax and the effcient level of public good provision in a setting where the policy maker maximizes an inequality averse social welfare function and the agents' market ability is private information. The analysis points out that the terms added in the tax formulas due to the presence of Veblen effects might justify a reduction in the optimal marginal tax rates faced by the different individuals. Also, the desirability of negative marginal tax rates cannot be ruled out. With respect to the issue of the optimal level of public good provision, we derive a modfied Samuelson rule and highlight the fact that the Veblen-based part of the formula might require to distort downwards the efficient level of public good provision.
urn:nbn:se:uu:diva-100937
Keywords: H21; H23; H41; 330; optimal nonlinear income taxation; modified Samuelson rule; Veblen effects; Optimale Besteuerung; Einkommensteuer; Einkommensumverteilung; Konsuminterdependenz; Öffentliche Güter; Theorie